2011
DOI: 10.1021/jf203273y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Water Stability and Other Related Functional Properties of Thin Cast Kafirin Protein Films

Abstract: Improvement in the water stability and other related functional properties of thin (<50 µm) kafirin protein films was investigated. Thin conventional kafirin films and kafirinmicroparticle films were prepared by casting in acetic acid solution. Thin kafirin films cast from microparticles were more stable in water than conventional cast kafirin films.Treatment of kafirinmicroparticles with heat and transglutaminase resulted in slightly thicker films with reduced tensile strength. In contrast,glutaraldehyde trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 42 publications
(111 reference statements)
3
31
0
Order By: Relevance
“…Kafirin was extracted from a mixture of grain of two similar white, tan-plant non-tannin sorghum cultivars PANNAR PEX 202 and 606, as described (17). The protein was defatted and freeze-dried.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kafirin was extracted from a mixture of grain of two similar white, tan-plant non-tannin sorghum cultivars PANNAR PEX 202 and 606, as described (17). The protein was defatted and freeze-dried.…”
Section: Methodsmentioning
confidence: 99%
“…Various methods of cross-linking kafirin microparticles have been investigated to improve the water resistance of bioplastic films made from them (17). Cross-linking has also been investigated to improve the tensile properties of cast kafirin films (18) and cast zein films (19).…”
Section: Introductionmentioning
confidence: 99%
“…Similar reduction resistant bands were observed with kafirin microparticle films. 47 It has been suggested that the presence of polymeric kafirin resistant to reduction could be due to some covalent crosslinks being inaccessible to the reducing agent.…”
Section: Effects Of γ-Kafirin On the Chemical Structure Of Kafirin "Mmentioning
confidence: 99%
“…The films have a much smaller total surface area than the vacuolated kafirin microparticles. There is evidence that kafirin microparticle films are more resistant to digestive_proteolytic enzymes (40.7% digested after 2 h) 16 than kafirin microparticles (86% digested after 2 h) 14 and so may be more inert when used as an implant in a small animal model. Kafirin microparticle films crosslinked with two commonly used cross-linking agents, either glutaraldehyde or sorghum polyphenols were included to investigate any potential adverse effects of kafirin micropa1ticle films when treated with these potentially toxic cross-linking agents.…”
Section: Proteolysis (Ph Stat Ref) From the Normal Murine Tissue Of Amentioning
confidence: 99%
“…13 Kafirin can be formed into highly vacuolated micropmticles, between approximaterly l-1 0 [!In diameter, 14 providing a large surface area for binding bioactive compounds such as polyphenolic nutraceuticals, 15 and bone morphogenetic proteins (BMP's). 16 Thin (<50 [!In), water stable kafirin bioplastic films can also be formed from these micropmticles. 16 Both structures may have potential for scaffold type applications, since kafirin is slowly biodegraded by mammalian digestive proteolytic enzymes, 12 is non-allergenic, 17 and there is good evidence that kafirin is nontoxic to celiac sufferers.…”
Section: Introductionmentioning
confidence: 99%